Christopher Brumfit Thesis Award Winner 2014 – Hilde van Zeeland: Four studies on vocabulary knowledge in and from listening: Findings and implications for future research. (21st December 2016) - van Zeeland, Hilde
Abstract : This paper discusses four studies from a recently completed Ph.D. thesis (van Zeeland, 2014a ) on L2 listening and vocabulary knowledge. Two studies focused on the recognition of spoken vocabulary knowledge in isolation and in context, as well as the assessment of it, and two studies explored lexical inferencing and incidental vocabulary acquisition from listening. This paper summarises the main findings and discusses implications for future research. Together, the studies emphasise the need for more research attention to spoken vocabulary knowledge, especially in continuous speech. They also show how listening could contribute to expanding vocabulary knowledge, and emphasise several factors that future research on this topic should take into account.